The Effect of Education Quality and Tuition Fees on School Selection Decisions Through Mediation of School Image at Citra Bangsa School Tangerang - Stephanie Tjay; Widi Dewi; Teguh Widodo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Basic education serves as a crucial foundation in shaping an individual's mindset and character. The demographic bonus in Indonesia presents an opportunity for schools to compete as the preferred choice for parents and students. The rapid development of technology and easy access to learning resources encourage schools to reassess their position in the eyes of parents. The phenomenon of school selection has become increasingly complex, influenced by perceptions of educational quality, educational costs, and the school's image within the community. This study aims to analyze the influence of Educational Quality and Educational Costs on School Selection Decisions, with School Image as a mediating variable. This research employs a quantitative method with primary data obtained through questionnaires distributed to 532 parents of students at SD Citra Bangsa School. Using the Slovin formula, a sample of 229 respondents was obtained. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the Smart PLS 3.0 application. The results show that Educational Quality has a positive and significant effect on School Image and School Selection Decisions. Additionally, Educational Costs have a positive and significant effect on School Image and School Selection Decisions. School Image also has a positive and significant influence on School Selection Decisions. Furthermore, both Educational Quality and Educational Costs have a positive and significant impact on School Selection Decisions through School Image as a mediating variable. These findings highlight the importance of educational quality and educational costs in influencing parents' decisions when choosing schools for their children.